CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND STUDENTS’ SPEAKING ABILITY AT VIII GRADE OF SMP NEGERI 4 GAUNG ANAK SERKA - Trinovangke Fatimah; Sri Erma Purwanti; Agus Mustajib (J-Shelves of Indragiri (JSI), 2019)
The purpose of this study was to investigate the correlation between students' vocabulary mastery as the independent variable and speaking ability as the dependent variable. The sample of this study were 38 students of eighth-grade students of SMPN 4 Gaung Anak Serka. The research method used in this study was a correlation study. The researcher gave tests of vocabulary and speaking ability to collect data. After the data has been collected, it was found that the average of students' vocabulary mastery is 42.7, it was in the very low category, and the average of students' speaking ability was 36.5, also in the very low category, it was in the range 00 – 49. Based on those findings, the researcher analyzed the relationship between the students' vocabulary mastery and speaking ability using the Pearson Product Moment formula, the results was 0.339 it was classified as low correlation. Then to test the hypothesis, the researcher compared the values of rxy = 0.339 and rtable = 0.2709 (5%) and 0.3202 (1%). In short, 0.2709 < 0.3393 > 0.3202. Meanwhile, the SPSS result has also proven that the Sig. (2-tailed) was 0.037, which was less than 0.05. Dealing with the results, it could be determined that Ho (null hypothesis) was rejected, and H1 (alternative hypothesis) was accepted. It means that there is a positive and significant correlation between vocabulary mastery and speaking ability. If students have good vocabulary so that they will have a good speaking ability.